2022
DOI: 10.1017/s0031182022000099
|View full text |Cite
|
Sign up to set email alerts
|

A review of the current status of Cryptosporidium in fish

Abstract: Species of the genus Cryptosporidium (phylum Apicomplexa) infect the epithelium of the gastrointestinal tract of several vertebrate hosts, including humans and domestic and wild animals. In the past 20 years, several studies have focused on Cryptosporidium in fish. To date, a total of four piscine-host-specific species (Cryptosporidium molnari, Cryptosporidium huwi, Cryptosporidium bollandi and Cryptosporidium abrahamseni), nine piscine genotypes and more than 29 unnamed genotypes have been described in fish h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 79 publications
(222 reference statements)
1
9
0
Order By: Relevance
“…Both Eimeria and Cryptosporidium colonization in the intestinal system of Asian seabass were evident by microscopic observation and PCR amplification of the 18S rRNA gene. Phylogenetic analysis in this study showed the considerable genetic distance between piscine‐ and other higher vertebrate host‐derived isolates of Cryptosporidium and Eimeria species, which was consistent with previous studies (Couso‐Pérez et al., 2019, 2022; Ryan et al., 2015; Zanguee et al., 2010). Thai Cryptosporidium sp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both Eimeria and Cryptosporidium colonization in the intestinal system of Asian seabass were evident by microscopic observation and PCR amplification of the 18S rRNA gene. Phylogenetic analysis in this study showed the considerable genetic distance between piscine‐ and other higher vertebrate host‐derived isolates of Cryptosporidium and Eimeria species, which was consistent with previous studies (Couso‐Pérez et al., 2019, 2022; Ryan et al., 2015; Zanguee et al., 2010). Thai Cryptosporidium sp.…”
Section: Discussionsupporting
confidence: 92%
“…detected in the present study was comparable to the prevalence of C. scophthalmi in juvenile turbot ( Scophthalmus maximus ), while the lower prevalence of <15% was observed in the larger fish (Alvarez‐Pellitero et al., 2004). Although the prevalence of coccidia infection in the fish intestine was considerably variable among cultured systems, fish species and fish size, the pre‐grow out and early‐grow out stages were reported to be the most remarkable stages that were infected with coccidia, corresponding to the high intensity of infection (Couso‐Pérez et al., 2022; Gjurčević et al., 2017; Reghaissia et al., 2022; Sitjà‐Bobadilla et al., 2005). The high infection intensity in the 60‐day fish implied that younger fish have a weaker immune response than adults, resulting in less protection against parasites (Hrubec et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other gregarine-related parasites infecting aquatic hosts, such as Cryptosporidium spp. found in fish, also exemplify intracellular cell development in which the sporogonial part takes place in parasitophorous vacuoles deeply nested within the cytoplasm of the epithelial cells, in contrast to all other cryptosporidians in vertebrates where development takes place in apical position attached to the epithelial cells (Alvarez-Pellitero and Sitjà-Bobadilla 2002; Couso-Pérez, Ares-Mazás, and Gómez-Couso 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium is a zoonotic gastrointestinal parasite, which can infect a broad range of hosts [ 63 , 64 ]. Cryptosporidium infection among reptiles mainly presents as a gastroenteritis-like syndrome [ 65 , 66 , 67 ] and disease severity ranges from mild to severe, with symptoms varying based on the site of infection and the host’s dietary and immunological state [ 65 ].…”
Section: Discussionmentioning
confidence: 99%